Implementation Of Psak 22: Business Combination Impact Analysis Of The Indonesian Sharia Bank Merger - Farman, Fanji (LPPM Universitas Sebelas April, 2024)
The aim of this research is to determine the impact of the merger between three sharia banks in Indonesia, namely Bank BRISyariah, Bank Syariah Mandiri, and Bank BNI Syariah. The merger between three sharia banks in Indonesia is one of the largest mergers in the history of sharia banking in Indonesia. Meanwhile, the sample for this research is three sharia banks that have merged in Indonesia, namely Bank Syariah Mandiri, Bank Muamalat Indonesia, and Bank BRI Syariah. The data obtained from in-depth interviews and document studies will be processed using qualitative analysis techniques, such as content analysis and narrative analysis. In terms of financial performance, the research results show that the merger between three sharia banks in Indonesia has had a positive impact on the financial performance of the resulting banks. mergers. In terms of operational performance, the research results show that the merger between three Islamic banks in Indonesia has had a positive impact on the operational performance of the merged bank. In order to increase the effectiveness and efficiency of sharia bank mergers in Indonesia, several suggestions for further research are as follows: First, further research can analyze the factors that influence sharia bank merger decisions in Indonesia in more depth. Further research can be a reference for Islamic banks in Indonesia in making appropriate and effective merger decisions, as well as ensuring the success of mergers in increasing efficiency, stability and competitiveness of the Islamic banking industry.